(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
While feeding rats with Glycyrrhiza glabra the activity of enzymes of proline biosyntesis in different organs of rats decreases considerably. While feeding with Glycyrrhiza glabra of rats with incision of nervus shiacic brings to sharp growth of activity of arginase and enzymes of proline biosynthesis. Obviously, during regeneration the activity of non-ureote!ic isoenzymes of arginase increases, functioning in enzymatic system of proline biosynthesys from arginine through ornithine. In kidneys under the impact of Glycyrrhiza glabra an increase of activity of arginase and enzymes of proline biosynthesis takes place. A greater increase of activity of these enzymes is observed while feeding with Glycyrrhiza glabra of the rats with incision of nervus shiacic.